(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This paper deals about the quick changes in the constitution of a familiar pattern and other topics of female sexual moral, between the late nineteenth and early twentieth centuries. It attempts to identify the mechanisms that led women to adopt a more rigid sexual moral, with stereotyped forms of generic relations and a passive, subordinated role of women. Through a "great man" of Pampas, as a "guardian" of the local young women -as showed in the thirty-four letters written between August 1903 and september 1904- we analyzed the relationships among the “honourable residents" of the community, and the moral principles exalted in the speech.